LEGAL MATTERS OF ESTABLISHING TERRITORIAL STRUCTURES OF EXECUTIVE POWER CENTRAL BODIES IN THE UNITED STATES - M. A. Zakharova (Гуманитарные и юридические исследования, 2021)
The article discusses the experience of the legal organization of the territorial bodies of Central Executive power in the United States with the establishment of the conditional management areas, unifying a territory of a certain number of states, and placing them in regional offices of Federal Executive authorities and in some cases the subordinate territorial units. It is aimed at optimizing the Federal government and improving the effectiveness and efficiency of the central executive power.